Pharmacological properties of protocatechuic acid and its potential roles as complementary medicine - Semaming Y. (Hindawi Publishing Corporation, 2015)
© 2015 Yoswaris Semaming et al. This paper reviews the reported pharmacological properties of protocatechuic acid (PCA, 3,4-dihydroxy benzoic acid), a type of phenolic acid found in many food plants such as olives and white grapes. PCA is a major metabolite of anthocyanin. The pharmacological actions of PCA have been shown to include strong in vitro and in vivo antioxidant activity. In in vivo experiments using rats and mice, PCA has been shown to exert anti-inflammatory as well as antihyperglycemic and antiapoptotic activities. Furthermore, PCA has been shown to inhibit chemical carcinogenesis and exert proapoptotic and antiproliferative effects in different cancerous tissues. Moreover, in vitro studies have shown PCA to have antimicrobial activities and also to exert synergistic interaction with some antibiotics against resistant pathogens. This review aims to comprehensively summarize the pharmacological properties of PCA reported to date with an emphasis on its biological properties and mechanisms of action which could be therapeutically useful in a clinical setting.